Early Warning of Longwall Weighting Events and Roof Cavities Using Lva Software - David I. Hoyer (International Conference on Ground Control in Mining, 2011)
It is shown that by monitoring longwall leg pressures in real time, warning can be given for significant weighting events and the formation of roof instabilities, such as roof cavities, several hours in advance. Longwall Visual Analysis (LVA) is a software package that continuously monitors shield pressures and shearer position in longwall mines. LVA has been running on 19 Australian longwalls for up to four years, and as a result a very substantial database of shield pressure trends in a wide range of longwall situations has been collected. This database has been analyzed to develop indicators that will give operators and geotechnical engineers advance warnings of developing conditions such as weighting events and difficult roof conditions. LVA displays live charts of data, such as shield leg pressures, loading rates, and yield frequencies. Data analysis techniques were applied to historical data records from multiple longwall sites in order to develop a ?Cavity Risk Index? (CRI). The CRI indicates the risk of roof cavities developing, and it is based on pressure trends that indicate significant yielding and loading rates spanning a region of relatively low support. Case studies from different longwalls are given, showing how the CRI can give real-time advance warning of the formation of roof cavities with their anticipated location on the face. The limited number of case studies done so far indicate that the predictions have a high degree of reliability, but more work is required to quantify this.